Artificial intelligence for data-driven medical diagnosis - Bhattacharyya, Siddhartha; Gupta, Deepak; Kose, Utku; Le Nguyen, Bao (Intelligent Biomedical Data Analysis ;, 2021)
This book collects research works of data-driven medical diagnosis done via Artificial Intelligence based solutions, such as Machine Learning, Deep Learning and Intelligent Optimization. Physical devices powered with Artificial Intelligence are gaining importance in diagnosis and healthcare. Medical data from different sources can also be analyzed via Artificial Intelligence techniques for more effective results.